2010
DOI: 10.1073/pnas.1004519107
|View full text |Cite
|
Sign up to set email alerts
|

Replenishment of fish populations is threatened by ocean acidification

Abstract: There is increasing concern that ocean acidification, caused by the uptake of additional CO 2 at the ocean surface, could affect the functioning of marine ecosystems; however, the mechanisms by which population declines will occur have not been identified, especially for noncalcifying species such as fishes. Here, we use a combination of laboratory and field-based experiments to show that levels of dissolved CO 2 predicted to occur in the ocean this century alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
491
5
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(520 citation statements)
references
References 37 publications
23
491
5
1
Order By: Relevance
“…By contrast, fish were initially believed to be safe from the effects of OA, as early studies demonstrated a lack of mortality under extremely high CO 2 levels (greater than 10 000 matm) [5]. However, an increasing body of evidence suggests that OA-relevant CO 2 /pH levels induce various sublethal effects in fish, including otolith over-growth [6,7], a shift in behavioural lateralization [8,9], alterations in olfaction that affect detection of cues from substrates, parents [10], prey [11] and predators [8,12,13], and impaired learning [9,14]. Because the gamma-aminobutyric acid type A (GABA A ) receptor antagonist, gabazine, restores proper discrimination of predator odour, learning of predatory cues [14] and behavioural lateralization in OA-exposed fish [8], at least some of the deleterious effects of OA in fish seem to be related to altered neurotransmitter function.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, fish were initially believed to be safe from the effects of OA, as early studies demonstrated a lack of mortality under extremely high CO 2 levels (greater than 10 000 matm) [5]. However, an increasing body of evidence suggests that OA-relevant CO 2 /pH levels induce various sublethal effects in fish, including otolith over-growth [6,7], a shift in behavioural lateralization [8,9], alterations in olfaction that affect detection of cues from substrates, parents [10], prey [11] and predators [8,12,13], and impaired learning [9,14]. Because the gamma-aminobutyric acid type A (GABA A ) receptor antagonist, gabazine, restores proper discrimination of predator odour, learning of predatory cues [14] and behavioural lateralization in OA-exposed fish [8], at least some of the deleterious effects of OA in fish seem to be related to altered neurotransmitter function.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple species of fish, for example, fail to properly process waterborne cue information when confronted with the scent of predators [5,6]. Such impaired behaviours appear to originate from altered neurotransmitter and ion channel function under conditions of reduced seawater pH [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Potential impacts include changes in calcification, fecundity, organism growth and physiology, species composition and distributions, food web structure, and nutrient availability (Doney et al, 2012;Fabry et al, 2008;Iglesias-Rodriguez et al, 2008;Munday et al, 2009Munday et al, , 2010. Within this century, the impacts of ocean acidification will increase in proportion to emissions (Gattuso et al, 2015).…”
Section: Introductionmentioning
confidence: 99%